Comparison of four immunoassays to measure serum ferritin concentrations and iron deficiency prevalence among non-pregnant Cambodian women and Congolese children - Karakochuk, Crystal D.; Whitfield, Kyly C.; Rappaport, Aviva I.; Barr, Susan I.; Vercauteren, Suzanne M.; McLean, Judy; Hou, Kroeun; Talukder, Aminuzzaman; Houghton, Lisa A.; Bailey, Karl B.; Boy, Erick; Green, Timothy J. (Walter de Gruyter GmbH, 2017)
Global standardization of ferritin assays is lacking, which could have direct implications on the accurate measurement and comparability of ferritin concentration and iron deficiency (ID) prevalence rates in at-risk populations.We measured serum ferritin concentrations using four immunoassays: the s-ELISA and the AxSYM™ analyzer were compared among 420 non-pregnant Cambodian women; the Centaur® XP analyzer, s-ELISA, and AxSYM™ analyzer were compared among a subset of 100 Cambodian women; and the s-ELISA and the Elecsys® 2010 analyzer were compared among 226 Congolese children aged 6–59 months.Median ferritin concentrations (adjusted for inflammation) ranged between 48 and 91 μg/L among Cambodian women and between 54 and 55 μg/L among Congolese children. ID prevalence ranged from 2% to 10% among Cambodian women and 5% to 7% among Congolese children. Bias between methods varied widely (–9 to 45 μg/L) among women, and was 43 μg/L among children. Bias was lower when ferritin values outside of the s-ELISA measurement range (>250 μg/L) were excluded.The observed differences in ferritin concentrations likely reflect different ferritin isoforms, antibodies, and calibrators used across assays and by different laboratories. However, despite differences in ferritin concentrations, ID prevalence was relatively similar and low across all methods.